1998
DOI: 10.1074/jbc.273.2.1114
|View full text |Cite
|
Sign up to set email alerts
|

Functional Calcium-sensing Receptors in Rat Fibroblasts Are Required for Activation of SRC Kinase and Mitogen-activated Protein Kinase in Response to Extracellular Calcium

Abstract: Changes in the concentration of extracellular calcium can affect the balance between proliferation and differentiation in several cell types, including keratinocytes, breast epithelial cells, and fibroblasts. This report demonstrates that elevation of extracellular calcium stimulates proliferation-associated signaling pathways in rat fibroblasts and implicates calcium-sensing receptors (CaR) as mediators of this response. Rat-1 fibroblasts express CaR mRNA and protein and respond to known agonists of the CaR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 33 publications
6
129
1
2
Order By: Relevance
“…There are numerous reports showing the CaSRs' effect on cell proliferation in many cell types including myeloma (Yamaguchi et al, 2002), ovarian surface epithelial cells (Hobson et al, 2000), fibroblasts (McNeil et al, 1998) and osteoblasts (Dvorak et al, 2004). We also studied the CaSRstimulated mesangial proliferation ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous reports showing the CaSRs' effect on cell proliferation in many cell types including myeloma (Yamaguchi et al, 2002), ovarian surface epithelial cells (Hobson et al, 2000), fibroblasts (McNeil et al, 1998) and osteoblasts (Dvorak et al, 2004). We also studied the CaSRstimulated mesangial proliferation ( Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the current findings that the CaSR activation evokes a mitogenic effect on the MMCs further support the notion that the CaSR is involved in this physiological process in a variety of cell types. Elevated CaSR expression may contribute to the action of growth signaling pathways, including mitogen-activated protein kinase (McNeil et al, 1998;Yamaguchi et al, 2002). In addition, many reports have shown that several protein kinases affect the CaSR-induced signaling cascades (Awata et al, 2001;Sakwe et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the stem cell may be able to recognize that extracellular calcium content. The calcium-sensing receptor (CaR) 17 is a seven membrane spanning receptor that does not serve as a channel to transport calcium, but recognizes extracellular calcium. In a null mouse model, in the absence of this receptor, the stem cells were unable to engraft at the endosteal surface in a competitive setting (see Figure 1).…”
Section: Role Of Extracellular Matrix Componentsmentioning
confidence: 99%
“…Changes in extracellular calcium are monitored by the ubiquitously expressed extracellular calcium-sensing receptor (CaR) (43,44). Calcium-or agonist-induced activation of this G protein-coupled receptor has been linked to activation of various MAP kinases, including ERK1/2 (45)(46)(47). Our preliminary data suggest that CaR activation with the polycationic agonist Gd 3ϩ can also induce MMP-9 gene expression (data not shown), suggesting that signaling through the CaR may control MMP-9 expression in premalignant oral keratinocytes.…”
Section: P38 Mapk Negatively Regulates Mmp-9 In Oral Cancermentioning
confidence: 99%